2000
DOI: 10.2307/3434998
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality and Reproductive Health of Young Czech Men Exposed to Seasonal Air Pollution

Abstract: This study of male reproductive health in the Czech Republic resulted from community concern about potential adverse effects of air pollution. We compared young men (18 years of age) living in Teplice, a highly industrialized district with seasonally elevated levels of air pollution, to those from Prachatice, a rural district with relatively clean air. Surveys were scheduled for either late winter, after the season of higher air pollution, or at the end of summer, when pollution was low. Participation included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 12 publications
4
65
0
5
Order By: Relevance
“…37 Studies have suggested that exposure to ambient air pollution is associated with defects in several measures of semen quality. [38][39][40] Therefore, according to the previous studies mentioned above, air pollution at maternal and paternal residences might be assumed to be a proxy for SAB.…”
Section: Discussionmentioning
confidence: 99%
“…37 Studies have suggested that exposure to ambient air pollution is associated with defects in several measures of semen quality. [38][39][40] Therefore, according to the previous studies mentioned above, air pollution at maternal and paternal residences might be assumed to be a proxy for SAB.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that spermatogenesis is particularly sensitive to environmental attacks of physical or chemical nature in working settings (De Rosa et al, 2003;Sheiner et al, 2003;Jensen et al, 2006). Moreover, some studies (Adamopoulos et al, 1996;Sram et al, 1996Sram et al, , 1999Selevan et al, 2000;Rubes et al, 2005) have reported the potential relationship between the continuous deterioration in the long run of the air pollution indices and the declining main sperm parameters with consequential impaired reproductive function in male population. Specifically, Rubes et al (2005) found that the percentage of spermatozoa with DNA fragmentation was significantly associated with air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the detrimental effects of air pollution in general environment on male reproductive health are still scanty and not conclusive. In a study (Teplice program), Sram et al (1996Sram et al ( , 1999 observed that exposure to high levels of airborne fine particle pollution may be associated with transient decrements in the main sperm parameters, mainly morphology (Selevan et al, 2000), and with sperm DNA damage (Rubes et al, 2005). Also Adamopoulos et al (1996) observed a significant decline in seminal volume and total sperm number over a 17-year period in a homogeneous population living under the same continuously deteriorating environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous published studies have compared patients with male infertility (oligospermia or azoospermia) to healthy subjects (normal sperm count). To date, proposed risk factors include air temperature [10], automobile driving time per day [11], air pollution [12], regional differences in residential population density [13], mumps [14], stress [15], alcoholism [16] and smoking [17]. This has indicated a particular vulnerability of the fetal testis to toxicants-for instance, maternal tobacco smoking [18].…”
Section: Human Male Infertility and Environmental Factorsmentioning
confidence: 99%